THE EFFECT OF TRANSFORMATIONAL LEADERSHIP OF EDUCATION CENTER COMMANDERS TOWARDS READINESS FOR CHANGE IN EDUCATORS AT THE INDONESIAN ARMY EDUCATION CENTER - Hadi Guntoro; Endah Andriani Pratiwi (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2022)
The Indonesian Army (Tentara Nasional Indonesia Angkatan Darat or TNI AD) must have good quality education to face challenges in the era of the industrial revolution 4.0, so military educators must be ready to change and develop learning innovations that are in line with the current needs of the Indonesian National Armed Forces (TNI). Transformational leadership is the most appropriate leadership style for change effectiveness. This study focuses on how transformational leadership affects educators' readiness to change learning methods. This research is a deductive quantitative research using a non-experimental design with a causal type of research. The research subjects are 174 military educators. The primary data collection strategy was a questionnaire. The questionnaire is an adaptation of Angela Ganni's questionnaire based on the theory of Bass & Riggio for transformational leadership while the readiness of the educators for change is based on the theory of Holt. Data analysis using multiple regression and descriptive statistics. The results showed that transformational leadership has no significant effect on military educators’ readiness to change. Leaders did not give personal attention and treated each member individually. Most of the military educators’ readiness to change was found in the medium category.